Pengaruh Senam Hamil Yophytta Terhadap Skala Nyeri Punggung Bawah (Low Back Pain) Pada Ibu Hamil Trimester II Dan III Di Kantor Pusat Senam Hamil Yophytta Maternal Surabaya: Penelitian Pra Eksperimental - Aulia Pradita (2010)
Low back pain in pregnancy may be complained by women in second and third trimesters. It is caused by increase in body weight and hormonal changes in pregnancy. Increase in body weight lead to changes in centre of mass (COM) that causes lordosis progressive. In the end of pregnancy period progesteron and relaxin increase, their role is to relax and loosen the tissues of body in order to help prepare for childbirth. This is causes however shifting of the joints and laxity in the muscles and ligaments in pelvis and resulting in low back pain. Thus pregnant women are suggested to do exercise regularly to reduce the pain. The aim of this study was to investigate the influence of Yophytta Maternal exercise on the low back pain scale in second and third trimesters of pregnancy. This study used pre-experimental one-group pre-post test design with non probability sampling (purposive sampling). Sample comprised of 9 respondents who fit the inclusion criteria. All respondents in this study participated in 4 weeks program of Yophytta maternal exercise at Central Office of Yophytta Maternal exercise Surabaya. Average low back pain intensity were measured using Bourbonais pain scale. Data collected before and after the exercise and analyzed using Wilcoxon Signed Rank Test with significance level of p ≤ 0.05. The result showed that 4 weeks Yophytta maternal exercise can reduce the average low back pain intensity scale with significant level of p = 0.006. It can be concluded that low back pain intensity scale in second and third trimesters of pregnancy can be reduced by regular 1,5 hour Yophytta maternal exercise for 4 weeks.